2002
DOI: 10.1177/104687810203300303
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Strategic Competence: What Simulations Can Do for You

Abstract: This article integrates major outcomes of a simulation-based approach to teaching foreign language and links it to learners’attainment of strategic competence. According to existing research, curricula inspired by the approach seem to promote favorable conditions for language acquisition. If language teachers design simulations that help learners to assess the characteristics of the language situation, set communicative goals, plan responses, and control the execution of their plans, they help learners to beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
1
4
0
1
Order By: Relevance
“…A third benefit was that the simulation promoted the students’ abilities as critical thinkers as it encouraged them to explore multiple perspectives on the issue and construct a well-supported argument. The instructors’ responses corroborate the benefits that Salies (2002a) found in using language simulations in an EAP writing classroom — selecting, critiquing, comparing, and transferring information as part of students’ argument construction. This conclusion also supports the views of Crookall and Oxford (1990) who argued that language simulations enable learners to explore and generate abstract ideas.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…A third benefit was that the simulation promoted the students’ abilities as critical thinkers as it encouraged them to explore multiple perspectives on the issue and construct a well-supported argument. The instructors’ responses corroborate the benefits that Salies (2002a) found in using language simulations in an EAP writing classroom — selecting, critiquing, comparing, and transferring information as part of students’ argument construction. This conclusion also supports the views of Crookall and Oxford (1990) who argued that language simulations enable learners to explore and generate abstract ideas.…”
Section: Resultssupporting
confidence: 59%
“…While for some students in IC1 the simulation represented their first entry into research, the students in IC2 refined their information searching abilities. The instructors’ and the students’ attitudes to the simulation confirm the value of experiential learning in mobilizing the students to gather, evaluate, and retain new information more effectively (Garcia-Carbonnell et al, 2001; Naidu, 2007; Salies, 2002a, 2002b). As Salies (2002b) observed, simulations which draw on timely issues are attractive to students.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…It is therefore not surprising that researchers have found that the gap between reading comprehension, speaking, and writing can be often bridged by engaging secondlanguage learners in simulations [7]. Previous studies also concur that simulations may provide learners with a relatively stress-free and meaningful learning environment in which they can apply discipline specific contents and develop language skills simultaneously [11]- [13]. These benefits, highlighted by recent applications of simulation tasks to language content-based education in other disciplines [14], [15], encouraged our team to implement a series of simulations to better support student learning in our design course.…”
Section: Introductionmentioning
confidence: 99%